Caracterização química e sensorial de bebida mista de soja e uva - Brunelli, Luciana Trevisan [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP] (My University, 2012)
The aim of this study was to produce mix beverages of grape juice and soybean hydrosoluble extract (SHE) in laboratory scale. The raw materials were soybean (variety BRS 213), grape (species Vitis labrusca, variety Niagara Rosada), citric pectin, water and sugar. The mix beverage was produced with different proportions of SHE and grape juice (1:1; 1:1.5 and 1:2; respectively; m/m) and different soluble solids concentrations (10, 12 and 14 °Brix) obtained by adding granulated sugar (sucrose). Soybean hydrosoluble extract, grape juice and mix beverages were chemically analyzed (humidity, ash, protein, lipids, carbohydrate, reducing sugars, total reducing sugars, sucrose, titratable acidity and pH). The mix beverages were sensorial analyzed through the acceptance test (hedonic scale). The results of chemically analyzed were expressed as mean and standard deviation and the results of sensorial analyzed were submitted to variance analysis and the means were compared using the Tukey test at 5% of probability. The pH of mix beverages was lower than 3.9, without addition of acidulants. Sugar addition to mix beverages (10; 12 and 14ºBrix) increased the levels of soluble solids, total reducing sugar and carbohydrates, but it did not interfere in the reducing sugar concentration. The increased proportion of grape juice in mix beverages allowed observing the elevation of titratable acidity and reducing sugars levels, as well as the pH reduction. The increase of grape juice in mix beverage did not interfere in the acceptance of mix beverages. The more sweetened beverages were preferred by the sensory panel.

O objetivo deste trabalho foi produzir bebida mista de suco de uva e extrato hidrossolúvel de soja (EHS), em escala de laboratório. As matérias-primas foram soja (cultivar BRS 213), uva (espécie Vitis labrusca, variedade Niágara Rosada), pectina cítrica, água e açúcar. A bebida mista foi fabricada com diferentes proporções de EHS e suco de uva (1:1; 1:1,5 e 1:2 m/m) e diferentes concentra- ções de sólidos solúveis (10, 12 e 14 °Brix), obtidas com a adição de açúcar cristal (sacarose). O EHS, suco de uva e as bebidas mistas foram analisados quimicamente (umidade, cinzas, proteína, lipídio, carboidrato, açúcares redutores (AR), açúcares redutores totais (ART), sacarose, acidez titulável e pH). As bebidas mistas foram analisadas sensorialmente por teste de aceitação (escala hedônica). Os resultados das análises químicas foram expressos como média e desvio padrão e os sensoriais foram submetidos à análise de variância e as médias foram comparadas pelo teste de Tukey ao nível de 5% de probabilidade. Todas as bebidas mistas produzidas apresentaram pH inferior a 3,9, sem adição de acidulantes. A adição de açúcar nas bebidas mistas (10; 12 e 14 ºBrix) causou elevação nos teores de sólidos solúveis, ART e carboidratos, mas não interferiu na concentração de AR. Com aumento da proporção de suco de uva na bebida mista, observou-se elevação dos teores de acidez titulável, açúcares redutores e redução do pH. O aumento da quantidade de suco de uva na formulação não interferiu na aceitabilidade das bebidas mistas. As bebidas mais adocicadas foram às preferidas pela equipe sensorial.
Chemical and sensorial characterization of mix beverage of soybean and grape
Keywords: Soybean milk; Grape juice; Chemical analysis; Sensorial analysis; EHS; Leite de soja; Suco de uva; Análise química; Análise sensorial